Maculolachnus blackmani (Hemiptera: Aphididae: Lachninae)—a new aphid species from India and Pakistan with key to species of the genus - Kanturski, Mariusz; Chakrabarti, Samiran (Zootaxa, 2022)
Apterous viviparous females of a new species of the Lachninae genus Maculolachnus Gaumont, 1920 from India and Pakistan are described here. The new species, Maculolachnus blackmani sp. nov. can be recognized among other representatives of this genus by stiff body setae with expanded or slightly flabellate apices in contrast to hair-like, fine and pointed setae in all other species. The similarities and differences from two other most common species of Maculolachnus—M. sijpkensi Hille Ris Lambers and M. submacula (Walker) have been compared. A key to apterous viviparous females of Maculolachnus is also presented.